Human rights & Islam in North-Western China : the effects of minority & religious policy in the Xinjiang Uyghur autonomous region - Holder, Ross (Trinity College (Dublin, Ireland). Department of Near and Middle Eastern Studies, 2016)
The Uyghur, one of China's 55 officially recognised minority nationalities, bear a distinct ethno-religious identity that demarcates them from China’s majority nationality, the Han. The Uyghurs' unique identity as a minority has resulted in the promulgation of laws and regulations in their homeland of Xinjiang that ostensibly seeks to integrate the Uyghurs into contemporary Chinese society. Since long prior to the establishment of the People's Republic of China in 1949, the underlying cultural differences between the Uyghur and the Han have contributed to a perception of otherness, resulting in a source of ethnic tension. More recently, Xinjiang has experienced heightened restiveness, with claims by Uyghurs of increased government repression, and assertions by the Chinese Communist Party of the growing threat of religious extremism. As a result of the increasingly volatile nature of Uyghur-Han interrelations within Xinjiang and beyond, the government has brought into force a series of policies, at both the national and municipal level, with the overt aim of combatting religious extremism. However, many Uyghur activists, human rights organisations and scholars argue that such policies are discriminatory in nature, serving as a covert vehicle for cultural assimilation.
Keywords: Languages, Literatures & Cultural Studies, Ph.D.; PhD Trinity College Dublin, 2016